Comparison of gated myocardial perfusion SPECT, echocardiography and equilibrium radionuclide ventriculography in the evaluation of left ventricle contractility - Filiz Hatipoğlu; Zeynep Burak; Özgür Ömür (KARE Publishing, 2014)
Objectives: In this study, we investigated the reliability of gated myocardial perfusion single-photon emission computerized tomography (GSPECT) for the evaluation of left ventricle (LV) function. We compared left ventricle ejection fraction (LVEF) calculated with GSPECT with the values derived from planar equilibrium-gated radionuclide ventriculography (ERVG) and echocardiography (ECHO). Study design: Forty-eight patients with suspected coronary artery disease (CAD), who were referred for evaluation of myocardial perfusion and LV function and underwent two-day 99mTc-MIBI protocol GSPECT and ERVG, were examined retrospectively. LVEF was calculated with GSPECT Myometrix software, and wall motion and thickness were calculated with QGS analysis program. In the ERVG study, LVEF values were calculated using left anterior oblique images. In the GSPECT and ERVG study, wall motion was evaluated visually and scored. LVEF values and wall motion data measured with ECHO were noted. Results: For all cases, there was a significant correlation between LVEF values calculated by GSPECT and ERVG. Numerical LVEF values of 30 patients measured with ECHO showed no significant difference from the values measured with GSPECT. When 240 segments obtained from 48 patients were examined, the correlation between GSPECT and ERVG was 77.5% and between GSPECT and ECHO was 75.4% by visual wall motion analysis. Quantitatively calculated wall motion and thickness scores of segments visually defined as normokinetic were significantly higher than segments visually defined as having contraction defect. Conclusion: GSPECT can be used safely in clinical practice for the evaluation of LV function. Quantitatively calculated wall motion and thickness scores are promising methods to verify the visual evaluation.